Secure data management : 4th VLDB Workshop, SDM 2007, Vienna, Austria, September 23-24, 2007 : proceedings - SDM; VLDB; Jonker, Willem; Petković, Milan (Lecture Notes in Computer Science, 2007)
This book constitutes the refereed proceedings of the Fourth VLDB 2007 International Workshop on Secure Data Management, SDM 2007, held in Vienna, Austria, September 23-24, 2007 in conjunction with VLDB 2007. The 11 revised full papers presented were carefully reviewed and selected from 29 submissions. The papers are organized in topical sections on Access Control, Database Security, Privacy Protection and Positon Papers.